Advances in Vehicular Networks - Masini, Barbara Mavì; Silva, Cristiano M.; Balador, Ali (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Connected and automated vehicles have revolutionized the way we move, granting new services on roads. This Special Issue collects contributions that address reliable and ultra-low-latency vehicular applications that range from advancements at the access layer, such as using the visible light spectrum to accommodate ultra-low-latency applications, to data dissemination solutions. Further, articles discuss edge computing, neural network-based techniques, and the use of reconfigurable intelligent surfaces (RIS) to boost throughput and enhance coverage.